2015
DOI: 10.1007/s00374-015-1026-z
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate production is mainly heterotrophic in an acid dairy soil with high organic content in Australia

Abstract: A laboratory incubation experiment was conducted using the nitrification inhibitor acetylene and 15 N isotope techniques in order to determine the relative significance of heterotrophic and autotrophic nitrification in three acid soils from different locations in Australia. The contribution of heterotrophic nitrification to total nitrification was found to vary from 20-88 % amongst the three soils. In the less acidic Glenormiston soil (pH w 6.2, organic C content 5.6 %), nitrification was largely autotrophic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Regarding the highest inhibitory effect on nitrification in dairy pasture soil, this may be due to nitrification in the dairy pasture soil being largely autotrophic. This can be supported by our previous study (Liu et al, 2015b) where we indicated that nitrification was primarily autotrophic with heterotrophic nitrification accounting for only 20%. In the alkaline sandy soil, C2H2 inhibition of NO3production was only 29%, thus 1% v/v of C2H2 may be insufficient to inhibit nitrification completely in this soil, nevertheless, most studies have indicated that this partial pressure of C2H2 is clearly sufficient for a complete inhibition.…”
Section: Inhibitory Effects Of C2h2 In Different Soilssupporting
confidence: 84%
“…Regarding the highest inhibitory effect on nitrification in dairy pasture soil, this may be due to nitrification in the dairy pasture soil being largely autotrophic. This can be supported by our previous study (Liu et al, 2015b) where we indicated that nitrification was primarily autotrophic with heterotrophic nitrification accounting for only 20%. In the alkaline sandy soil, C2H2 inhibition of NO3production was only 29%, thus 1% v/v of C2H2 may be insufficient to inhibit nitrification completely in this soil, nevertheless, most studies have indicated that this partial pressure of C2H2 is clearly sufficient for a complete inhibition.…”
Section: Inhibitory Effects Of C2h2 In Different Soilssupporting
confidence: 84%
“…DMPP was recently developed in Germany, and this inhibits nitrification at low concentrations of 0.5-1.0 kg active compound ha −1 ; this amount is less than one-tenth of the DCD applied [22]. erefore, the price of the urea fertilizer [27]) and animal manure (Dittert et al [28]; Hatch et al [29]; Maienza et al [30]). Shi et al [31] reported that DMPP slowed nitrification by inhibiting the growth of AOB, and DMPP application affected the abundance of AOB more than the ammonia oxidizer community composition.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia oxidation, as the rate-limiting step of nitrification, is catalyzed by AMO encoded by the amoA gene within the following two distinct groups of nitrifying microbes: ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) (BrochierArmanet et al 2008;Purkhold et al 2000). Of the available NIs, 3,4-dimethylpyrazole phosphate (DMPP) has been widely used together with synthetic N fertilizers (Weiske et al 2001;Di and Cameron 2011;Liu et al 2015) and animal manure (Hatch et al 2005;Fangueiro et al 2009;Maienza et al 2014). To achieve comparable effects, DMPP requires much lower application rates than other NIs such as dicyandiamide (DCD) (Chaves et al 2005;Chen et al 2008).…”
Section: Introductionmentioning
confidence: 99%